2012
DOI: 10.1152/ajplung.00291.2011
|View full text |Cite
|
Sign up to set email alerts
|

Role for TAK1 in cigarette smoke-induced proinflammatory signaling and IL-8 release by human airway smooth muscle cells

Abstract: Chronic obstructive pulmonary disease (COPD) is an inflammatory disease, characterized by a progressive decline in lung function. Airway smooth muscle (ASM) mass may be increased in COPD, contributing to airflow limitation and proinflammatory cytokine production. Cigarette smoke (CS), the major risk factor of COPD, causes ASM cell proliferation, as well as interleukin-8 (IL-8)-induced neutrophilia. In various cell types, transforming growth factor-β-activated kinase 1 (TAK1) plays a crucial role in MAP kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…Further studies should be preformed to clarify the role of RIP2 in cigarette smoke-related molecular signaling. It has been confirmed that cigarette smoke or CSE exposure could activate NF-κB phosphorylation and induce proinflammatory effects in aerodigestive cells [38,39]. Coincidentally, the present study indicated that cigarette smoke or CSE exposure up-regulated P-NF-κB expression in oral mucosa epithelium and Leuk-1 cells.…”
Section: Discussionsupporting
confidence: 81%
“…Further studies should be preformed to clarify the role of RIP2 in cigarette smoke-related molecular signaling. It has been confirmed that cigarette smoke or CSE exposure could activate NF-κB phosphorylation and induce proinflammatory effects in aerodigestive cells [38,39]. Coincidentally, the present study indicated that cigarette smoke or CSE exposure up-regulated P-NF-κB expression in oral mucosa epithelium and Leuk-1 cells.…”
Section: Discussionsupporting
confidence: 81%
“…This result indicates that another signaling pathway regulates ERK-mediated IL-6 expression. ERK is involved in many signaling pathways activated during immune responses, such as those associated with IL-8 expression (Pera et al, 2012), and asthma (Tacon et al, 2012;Yadav et al, 2006). Based on that ERK result, we modified our hypothesis.…”
Section: Discussionmentioning
confidence: 94%
“…Proliferation of human airway smooth muscle in response to PDGF is significantly reduced by the selective TAK1 inhibition, with a dominant-negative inhibitor and small molecule inhibitor, 5Z-7-oxozeaenol (Pera et al, 2011). TAK1 inhibition also inhibits cigarette smoke-induced release of CXCL8 from airway smooth muscle cells (Pera et al, 2012). H. influenzae activates NF-kB and p38 MAPK in human airway epithelial cells via the activation of TAK1 and NIK (Shuto et al, 2001).…”
Section: F Tgfb-activated Kinase-1 Inhibitionmentioning
confidence: 99%